Redescobrindo “Gonzaga Duque” por meio de sua produção escrita: edição de cartas pessoais e descrição de traços paleográficos - José Ferreira Filho (2023)
In this Dissertation, we bring at scene the writer “Luiz Gonzaga Duque Estrada” besides his activity as art critical, literate, journalism and writer, walked in Corte of the Rio de Janeiro and Portugal, registing, in your correspondences, your more human impressions, when he dialogue with fiancée/wife, relatives and friends. When we edit your personal letters, not only we reveal the intimate of social relations thought of his love, family and friendship letters, produced between finishes of the 19th century and beginning of the 20th, but also we glimpse paleographic and linguistcs features which singularize his textual production. We present twenty-six personal letters from Gonzaga Duque through of a semi-diplomatic and fac-similar edition, according to Spina (1977), Faria & Pericão (2008). From this edition, we turned specifically to description of paleographic traces, such as, morphology of the letters, angle, ductus, module and weight of the layout based in the orientations of Núñez Contreras (1998). We guided for theoretical and methodological assumptions of historical sociolinguistics with main goal of present the of Gonzaga Duque’ 19th and 20th century letters academic community in the light of the questions de authorship, authenticity, social and historical validity the manuscript sources of the Brazilian Portuguese (HERNÁNDEZ-CAMPOY & SCHILLING, 2012), according to Rumeu et alii (2019), Lima, Marcotulio & Rumeu (2019). The description of the morphology of the letters allow us identify graphemes whose forms are allographics, particularizing Gonzaga Duque’s writing. In linguistics terms, we identify morphosyntactic aspects of the vernacular of the Brazilian Portugueses such as the coexistence of the pronominal forms tu and você (RUMEU, 2013) and periphrastic future (OLIVEIRA, 2006). In synthesis, we proved from analysis of the analyzed paleographic traces, that the Gonzaga Duque’ letters are autograph sources of the Brazilian Portuguese write in 19th and 20th centures, which can surely lend reliability to future linguistic analyses.